Simultaneous Degradation of 30 Pharmaceuticals by Anodic Oxidation: Main Intermediaries and By-Products - Salazar-Gonzalez, R; Espinoza-Cisternas, L; Espinoza-Cisternas, L (Elsevier Ltd, 2021)
The anodic oxidation (AO) of 30 pharmaceuticals including antibiotics, hormones, antihistaminics, anti-inflammatories, antidepressants, antihypertensives, and antiulcer agents, in solutions containing different supporting electrolytes media (0.05 M Na2SO4, 0.05 M NaCl, and 0.05 M Na2SO4 + 0.05 M NaCl) at natural pH was studied. A boron-doped diamond (BDD) electrode and a stainless-steel electrode were used as anode and cathode, respectively, and three current densities of 6, 20, and 40 mA cm−2 were applied. The results showed high mineralization rates, above 85%, in all the tested electrolytic media. 25 intermediaries produced during the electrooxidation were identified, depending on the supporting electrolyte together with the formation of carboxylic acids, NO3−, SO42− and NH4+ ions. The formation of intermediates in chloride medium produced an increase in absorbance. Finally, a real secondary effluent spiked with the 30 pharmaceuticals was treated by AO applying 6 mA cm−2 at natural pH and without addition of supporting electrolyte, reaching c.a. 90% mineralization after 300 min, with an energy consumption of 18.95 kW h m−3 equivalent to 2.90 USD m−3. A degradation scheme for the mixture of emerging contaminants in both electrolytic media is proposed. Thus, the application of anodic oxidation generates a high concentration of hydroxyl radicals that favors the mineralization of the pharmaceuticals present in the spiked secondary effluent sample. © 2020 Elsevier Ltd